An Introduction to Issues in General Linguistics - Georgiou, Georgios P. (Cambridge Scholars Publisher, 2020)
This volume shows how the language system works in order to cultivate a correct attitude towards language, and to familiarize readers with the science of linguistics and issues related to it. All linguistic phenomena discussed here are accompanied by examples to allow the reader to understand how they are embedded in real linguistic contexts. The book discusses linguistic issues scientifically by considering findings from research studies.